Formation of the system of school education of the Kazakh society of central Kazakhstan in the second half of the XIX - the beginning of the XX centuries - Tuleuova, B.T.; Shotbakova, L.K.; Smagulova, G.M. (Sochi State University for Tourism and Recreation, 2018)
The article considers the formation and development of the system of school education in the Kazakh steppe in the context of the educational policy of the Russian Empire in the second half of the XIX and beginning of the XX centuries. Based on archival materials, various documents and scientific literature, the stages of formation and development of the school system of the Kazakh population are analyzed. The process of formation of the educational system is considered by the example of a nomadic society Akmola and Semipalatinsk regions, which constitute today the territory of Central Kazakhstan. Detailed in-depth analysis of archival data and documentary materials makes it possible to say that the formation of school education was complex, including various forms of organizing the education of Kazakh children, such as boarding schools, gymnasiums, Russian-Kazakh schools, and aul schools. The ultimate goal of the educational policy of the Russian Empire in the Kazakh steppe was, on the one hand, the commitment to bring out Kazakh children from the influence of Muslim ideology, on the other hand, the upbringing in Kazakh children a love for the Russian Empire as their homeland. In addition, educating of Kazakh children has of a purely pragmatic nature, since one of the goals of creating schools for Kazakh children was to train personnel for the administrative structures of the Russian Empire.
Keywords: educational policy; Kazakh society; Central Kazakhstan; Russian-Kazakh schools